Echogenic liposomes for ultrasound-triggered drug delivery - Izuchukwu, Ezekiel Charles (Rhodes University, Faculty of Science, Department of Chemistry)
Colorectal cancer is one of common cancers worldwide. It is the third most diagnosed cancer and the second leading cause of death. The use of 5-fluorouracil (5-FU) alone or in a chemotherapy regime has been the effective treatment of colorectal cancer patients. The efficacy of 5-FU in colorectal cancer treatment is significantly limited by drug resistance, gastrointestinal, and bone marrow toxicity through high-level expression of thymidylate synthase, justifying a need to improve its therapeutic index. Liposomes are colloidal membranes comprising of one or more lipid bilayers enclosing an aqueous core. They have been used to improve the therapeutic index of many anti-cancer drugs by changing drug absorption, elongating biological half-life, reducing metabolism, and reducing toxicity to healthy tissues. Echogenic liposomes are specifically designed to respond to external triggering like ultrasound stimulation by entrapping a gas or an emulsion that can vaporize. A liposome's unique property is that it can entrap both hydrophobic and hydrophilic substances simultaneously in the lipid bilayer and the aqueous core, respectively. These stimuli-responsive liposomes can be triggered externally with ultrasound, to release the chemotherapeutic cargo only at the required site. This research aims to formulate echogenic liposomes encapsulating 5-FU for potential ultrasound triggered release (echogenic). Liposome formulations wereprepared with lipid composition of crude soybean lecithin and cholesterol by thin-filmhydration method and the drug was passively loaded in the formulation. The 5-FU loadedliposomes were evaluated by dynamic light scattering (DLS) for particle size, polydispersityindex, and zeta potential and transmission electron microscopy (TEM) for morphology.Encapsulated liposomal formulations were also evaluated using physicochemical techniquesincluding thermogravimetric analysis (TGA), differential scanning calorimetry (DSC),Fourier-transform infrared spectroscopy (FTIR), and X-ray diffraction (XRD). Theencapsulation efficiency and release kinetics were studied using a validated high-performanceliquid chromatography (HPLC) method. Echogenic properties were explored by entrapping abiocompatible gas (argon) at the same time as the drug (5-FU) using a pressure/freezemethodology. The liposomal formulations were typically spherical with a size of about 150 nmand encapsulation efficiency of 62%. Low-frequency ultrasound (20 kHz) was used to triggerthe drug release from the complete formulation at 10%, 15%, and 20% amplitude and exposuretime of 5 min and 10 min. The rate of drug release from the nano-carrier was a function of theultrasound amplitude and exposure time and reached a maximum of 65% release under theconditions investigated. The cumulative release was investigated, with and without theapplication of ultrasound. It was demonstrated that the application of ultrasound resulted in complete release (99%) after 12 h while this dropped to 70% without ultrasound. These results are encouraging for optimizing ultrasound parameters for triggered and controlled release of the 5-FU, for conditions such as the management of cancer where low-power ultrasound can be applied.
Keywords: Liposomes; Drug delivery systems; Colon (Anatomy) -- Cancer -- Treatment; Transmission electron microscopy; Fourier transform infrared spectroscopy; Liquid chromatography; Echogenic liposomes; Ultrasound-triggered drug delivery